RETURN OF THE CULTURAL OBJECTS UNDER INTERNATIONAL LAW, EUROPEAN UNION LAW, AND LITHUANIAN LAW - Ravlusevicius, Pavelas (Revista Direitos Culturais, 2021)
The article examines the legal problems associated with the return of cultural objects in International, European Union, and Lithuanian Laws, as well as the extraterritorial application of mandatory norms. Particular importance is given to the influence of the UNIDROIT Convention on Stolen or Illegally Exported Cultural Objects and the Directive 2014/60/EC on the return of cultural objects unlawfully removed from the territory of a Member State. Attention is paid to the correlation of civil law doctrines with the protection of the owner’s rights and the bona fide purchaser of a cultural object on the one hand, and International and European Laws about the return to the owner and compensation to the owner of a cultural object on the other hand, because Lithuanian legislation and case law do not apply the vindication doctrine to protect owner’s rights of cultural objects and thus differs from the traditional approach to solving the problems of returning cultural objects within the civil law framework. The article deals with the related problems of recognition of the owner’s rights and changes in the evidence presumptions. The issue of restoring the owner’s rights to illegally confiscated cultural objects during the existence of the USSR was decided in the practice of the Constitutional Court of the Republic of Lithuania. Courts of general jurisdiction considered claims for the return of cultural objects belonging to foreign entities - the Federal Republic of Germany and the Prussian Cultural Heritage Foundation. Particular importance was the question of the application of International and European Laws in judicial practice. According to the results of the study of the practice of the Republic of Lithuania, it is proposed to regard the return of cultural objects as an independent way of protecting the owner’s rights, which makes secondary the bona fide purchaser doctrine in relation of a cultural object.